2017
DOI: 10.1136/bmjspcare-2016-001225
|View full text |Cite
|
Sign up to set email alerts
|

Health and death literacy and cultural diversity: insights from hospital-employed interpreters

Abstract: A value-based approach to ACP is recommended as a way to capture the person's individual values and beliefs. Health and death literacy have been identified as areas that may be over-estimated; areas that can be addressed and improved, if recognised. Health and death literacy is a particular area that needs to be assessed and addressed as a pre-requisite to ACP discussions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Another promising example of good practice is the Japanese educational program using stories as a primary learning tool, which showed that it is possible to deepen understanding among the lay public of the concept of end-of-life care through a narrative [ 9 ]. It is important that palliative care education initiatives be adapted to the cultural context of the environment where they are delivered, as highlighted by, e.g., Shen et al [ 42 ], Isaacson [ 43 ], Hayes et al [ 11 ], or in the Australian context by McGrath and Holewa [ 44 ]. The particulars for such adaptation, also in the Slovenian context, include the institutional and legal framework(s), organization of palliative care, and the level of public awareness of palliative care, as discussed above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another promising example of good practice is the Japanese educational program using stories as a primary learning tool, which showed that it is possible to deepen understanding among the lay public of the concept of end-of-life care through a narrative [ 9 ]. It is important that palliative care education initiatives be adapted to the cultural context of the environment where they are delivered, as highlighted by, e.g., Shen et al [ 42 ], Isaacson [ 43 ], Hayes et al [ 11 ], or in the Australian context by McGrath and Holewa [ 44 ]. The particulars for such adaptation, also in the Slovenian context, include the institutional and legal framework(s), organization of palliative care, and the level of public awareness of palliative care, as discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…A terminal or life-threatening illness is an illness or condition which cannot be cured and is likely to lead to someone’s death [ 9 ]. End-of-life care is defined as support for people who are in the last months or years of their life [ 11 , 12 ]. Last Aid comprises both palliative and end-of-life care, and offers support to patients who need long-term care or palliation to the very end of their lives, in life situations where death is known to be close, and in the dying process.…”
Section: Introduction [mentioning
confidence: 99%
“…The population serviced by this hospital is culturally diverse, with a high incidence of poor health literacy and people whose preferred language is not English 8 . Research has identified cultural difference in uptake of ACP and acceptance of treatment limitation 13–15 . Low health literacy has also been associated with lower acceptance of ACP and treatment limitation 1,16 .…”
Section: Discussionmentioning
confidence: 99%
“…While it is thought that in some cultures, discussing death openly is inappropriate out of a belief that 'bad things happen after you say them out loud' (Hayes et al 2020) or the belief that talking openly about death and dying is taking away the patient's hope (Hayes et al 2020), patients generally have their own preferences in talking about dying (Kirk et al 2004). It is important to carefully examine how patients talk about their death and to adjust communication about this topic to their communication style and information needs at that moment.…”
Section: Tipmentioning
confidence: 99%
“…Teachers may point out that many older migrants and older ethnic minorities(like many elderly) have had little formal education and therefore might have limited health literacy skills (Esser 2006) resulting in knowledge gaps about palliative care (Jansky et al 2019). This may be reinforced by the fact that migrants, while living most of their lives away from relatives and friends in their home country, may miss direct confrontations and experiences of seeing elderly with worsening conditions die (Hayes et al 2020). Patients with limited health literacy generally have limited understanding of end of life terminology such as malignant, terminal, prognosis, hospice, and palliative care (Ladin et al 2018).…”
Section: Introduce Health Literacy As An Important Factormentioning
confidence: 99%